1996
DOI: 10.1111/j.2042-3306.1996.tb01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus type 2: prevalence and seroepidemiology in foals

Abstract: Summary Whole blood and serum were collected from foals to determine the prevalence of Equine herpesvirus type 2 (EHV2) infection in foals, age at which infection can first be identified and serological responses to infection. Equine herpesvirus type 2 was isolated from peripheral blood mononuclear cells (PBMC) from 68 of 69 foals, 1–8‐months‐old, sampled once. Virus isolation was performed twice at intervals of 2–7 months on PBMCs from 33 foals and EHV2 was isolated on both occasions in all but one foal (nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 29 publications
3
34
0
4
Order By: Relevance
“…This observation warrant further investigations to establish the pathogenicity role of these EHV-5 strains. EHV-2, a member of the Gammaherpesvirinae closely-related to EHV-5, has been isolated in conjunction with other herpesviruses, in particular EHV-1 [30,44,46]. These authors reported cases of combined infection with members of the Alphaherpesvirinae (EHV-1) and Gammaherpesvirinae (EHV-2).…”
Section: Discussionmentioning
confidence: 89%
“…This observation warrant further investigations to establish the pathogenicity role of these EHV-5 strains. EHV-2, a member of the Gammaherpesvirinae closely-related to EHV-5, has been isolated in conjunction with other herpesviruses, in particular EHV-1 [30,44,46]. These authors reported cases of combined infection with members of the Alphaherpesvirinae (EHV-1) and Gammaherpesvirinae (EHV-2).…”
Section: Discussionmentioning
confidence: 89%
“…EHV-2 infection in young foals has been reported by others. 10,19 In the present study, samples were obtained from 11 foals from stable 1 3 times over a period of 6 months. All foals went through an active infection of EHV-2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 Most EHV-2 infections are either not associated with clinical signs or with signs of nonspecific illness, such as upper respiratory difficulty, poor performance, malaise, pyrexia, lymphadenopathy, granulomatous dermatitis, and immune suppression. 15,17,20 Despite its uncertain pathogenicity, EHV-2 has been proposed to be associated with keratoconjunctivitis and respiratory disease in foals. 4,7,15,17,20 Equid herpesvirus 2 has also been proposed to play a role in transactivation and possibly reactivation of EHV-1 and EHV-4, 23 as well as modulation of foal immune responses, predisposing them to Rhodococcus equi pneumonia.…”
mentioning
confidence: 99%
“…15,17,20 Despite its uncertain pathogenicity, EHV-2 has been proposed to be associated with keratoconjunctivitis and respiratory disease in foals. 4,7,15,17,20 Equid herpesvirus 2 has also been proposed to play a role in transactivation and possibly reactivation of EHV-1 and EHV-4, 23 as well as modulation of foal immune responses, predisposing them to Rhodococcus equi pneumonia. 16 As a cytopathogenic gammaherpesvirus, 21 EHV-2 is related to Human herpesvirus 4 (commonly known as Epstein-Barr virus).…”
mentioning
confidence: 99%